Proposed Federal State for the Bangsamoro: Level of Acceptance among the Bangsamoro Mujahidin - Najeeb Razul Sali; Nasrudin M. Datucali (Journal of Islamic Civilization, 2021)
This study was conducted to determine the level of acceptance among the Bangsamoro mujahidin on the proposed Bangsamoro federal state. Convenient and quota sampling were used among the 120 respondents identified for this study. It is found that most of the participants accepted the proposed federalism of the current government, though having some conditions. The regression analysis result showed that age was negatively correlated with their level of acceptance on the proposed federal state while educational attainment on both secular and Islamic schools was positively correlated with their response to the same provision statement. This study concluded that Bangsamoro mujahidin are now more welcoming to various alternative solutions to the Mindanao conflict within the framework of Philippine territorial integrity.